2012
DOI: 10.1007/s12355-011-0133-x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Sustaining Sugars in Sweet Sorghum Stalks During Post-Harvest Stage by Exploring Cultivars and Chemicals: A Desk Study

Abstract: In the recent years sweet sorghum is emerging as an important feedstock for bioethanol production. It was observed that total soluble sugar yield (TSSY) increases with time in the post-anthesis phase depending on the length of crop cycle. The qualitative and quantitative sugar loss of up to 50% or more occurs due to delay in harvest during post-physiological maturity stage depending on the genotype, weather and soil conditions, and the time lag between harvest and crushing of the stalks. Hence, a desk study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Thus, bmr and energy sorghum with high potential biomass yield can be used for bioethanol production. Sweet sorghum can also be promoted as a complementary feedstock in the sugar mill areas where sugarcane (Saccharum officinarum L.) is the popular feedstock (Srinivasarao et al, 2012).…”
Section: Biomass Compositionmentioning
confidence: 99%
“…Thus, bmr and energy sorghum with high potential biomass yield can be used for bioethanol production. Sweet sorghum can also be promoted as a complementary feedstock in the sugar mill areas where sugarcane (Saccharum officinarum L.) is the popular feedstock (Srinivasarao et al, 2012).…”
Section: Biomass Compositionmentioning
confidence: 99%
“…• The self fermentation of juice inside the stalk prior to juice extraction is a major concern, mainly when juice extraction is delayed after harvesting due to long distances prevailing between factory and the field. Preliminary results indicated that there will be reduction in sugar yield by 16.8 %, if the juice extraction is delayed by 48 h (Srinivasarao et al 2012). Research should therefore address the problem of post-harvest losses in terms of juice quality and quantity.…”
Section: The Sweet Sorghum Storymentioning
confidence: 99%
“…Preliminary results indicated that there will be reduction in sugar yield by 16.8 %, if the juice extraction is delayed by 48 h (Srinivasarao et al 2012). Research should therefore address the problem of post-harvest losses in terms of juice quality and quantity.…”
Section: The Sweet Sorghum Storymentioning
confidence: 99%